ANALISIS MANAJEMEN PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PENDIDIKAN KESETARAAN PAKET C DI PKBM BUANA MEKAR - Wawan Hermawan; Ardyanto Saputra; Rifki Permana Putra; Nadila Nuraini; Siti Azzahra Fauziah Triyanto (JCI Publisher, 2026)
Non-formal education plays an important role in providing educational services to communities unable to complete formal education. One form of non-formal education that serves as an alternative education is the Package C Equivalency Education Program. This study aims to analyze the implementation of the community empowerment management function through the Package C Equivalency Education Program at PKBM Buana Mekar Baleendah using the POAC (Planning, Organizing, Actuating, and Controlling) management approach. The study used a descriptive qualitative method with the research location at PKBM Buana Mekar, Bandung Regency. The research subjects consisted of PKBM managers, tutors, and Package C learners. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the planning function has been carried out through identifying community needs and preparing flexible learning programs. The organizing function is seen from the division of tutor tasks and a clear organizational structure. The implementation function is carried out through andragogy-based learning with lectures, discussions, questions and answers, and skills practice methods. Meanwhile, the supervisory function is carried out through learning evaluation, attendance monitoring, andsupervision of skills practice. Although the program's implementation has been quite successful, several obstacles remain, such as limited digital learning media, unstable student attendance rates, and suboptimal utilization of practical facilities. Overall, the Package C Program at Buana Mekar Community Learning Center (PKBM) has systematically implemented management functions to support the community empowerment process through equivalency education